Regulation of T-cell migration by co-stimulatory molecules. (25th October 2007) - David, R.; Marelli-Berg, F.M.
Abstract : Migration of primed T-cells to the antigenic site is an essential event in the development of effective immunity. This process is tightly regulated in order to ensure efficient and specific responses. Most studies have focused on non-specific mediators of T-cell migration, including integrins and chemokines. However, recent studies have highlighted the key role of the T-cell receptor and co-stimulatory molecules in guiding T-cell access to antigenic tissue. Here, we review the experimental evidence for an essential contribution of co-stimulation-mediated molecular interactions regulating T-cell migration in the development of T-cell immunity and tolerance.